Function, Fairness, and Feelings in Elementary Students’ Engineering Design Groupwork - Miel, Karen (Tufts Archival Research Center, 2020)
Youth who are learning engineering while participating in design teams are also learning to manage conflict. Engineering design teams regularly anticipate, encounter, and resolve disagreements about which tasks to pursue, which processes to utilize, and interpersonal interactions. Managing conflict while making design decisions is integral to engaging in and learning engineering in groups. Through phenomenographic analysis of interviews with 73 fourth- and fifth-grade students, this paper explores the ways in which these students experience and manage conflict in engineering design groupwork. Students describe the strategies and reasoning they employ to resolve task, process, and relationship conflict. When resolving conflict to make design decisions, these students consider the function of design solutions, the fairness of the group’s work process, and the feelings of group members. Youths’ experiences with and management of conflict have implications for their affective engagement, equitable participation, and persistence in engineering learning.; A qualifying paper submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Education.